Who speaks out, and about what? An examination of how physical education is portrayed in Norwegian news media - Laxdal, Aron; Aasen, Benjamin; Stensrud, Anna; Haugen, Tommy (Frontiers in Education, 2025)
This study examined how physical education is portrayed in Norwegian print media from 2012 to 2022. Using content analysis informed by agenda-setting and framing perspectives, 256 newspaper articles were analyzed to identify dominant voices and themes. The findings show that students and university faculty are the most visible contributors, while teachers are underrepresented, especially in national media. Coverage largely mirrors academic discussions and tends to frame physical education through health-related and expert-driven narratives, often linking the subject to broader social and political debates. Such portrayals may narrow public understanding by overshadowing physical education’s educational and formative purposes. The study discusses how media framing can shape perceptions of physical education’s role in education and health policy and underscores the need for more balanced representations to foster a broader and more informed public debate about its value in society.